Synthesis of nano-particles of CeO2 by auto-combustion method - Bang, Nguyen Dinh; Thuong Hue, Hoang Thi (Vietnam Journal of Chemistry, 2014)
Nano-particles of CeO2 with the smallest average particle size (from 10 to 20 nm) and uniform morphology, well- dispersion, especially with single crystal of CeO2 were obtained from a mixed solution of Ce(NO3)3, citric acid, polyvinyl ancohol by auto-combustion method. The synthesized CeO2 powders were characterized as the crystalline phase identification by X-ray diffraction (XRD), the morphology and particle size by trasmission electron microscopy (TEM), the single crystal of CeO2 was determinated by selected area electron diffraction (SAED).